2015
DOI: 10.1186/s12909-015-0396-0
|View full text |Cite
|
Sign up to set email alerts
|

Career intentions of final year medical students in Uganda after graduating: the burden of brain drain

Abstract: BackgroundUganda has severe shortage of human resources for health despite the heavy disease burden. The country has one of the highest fertility, and population growth rates in the world and is in dire need of trained health workers. The current doctor: patient ratio of 1:15000 is inadequate and this is further constrained by trained health workers leaving the country while others abandon the health sector. The aim of the study was to determine the career intentions of the final year medical students to leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 21 publications
5
50
1
2
Order By: Relevance
“…The results of present study showed that with increasing workload and reducing healthy work environment, the intention to immigration increases among nurses. Our study is consistent with similar studies in other countries that have identi ed high workload as one of the factors associated with nurses' intention to immigration (Lee and Moon, 2013;Kizito et al, 2015;Garner et al, 2015). In addition, a Inappropriate healthy work environment is one of the effective factors in maintaining nurses, and Inappropriate healthy work environment is one of the reasons related to the migration of nurses (Freeman et al, 2012;Dywili et al, 2013;Scruth et al, 2018;Hall et al, 2019;).…”
Section: Discussionsupporting
confidence: 91%
“…The results of present study showed that with increasing workload and reducing healthy work environment, the intention to immigration increases among nurses. Our study is consistent with similar studies in other countries that have identi ed high workload as one of the factors associated with nurses' intention to immigration (Lee and Moon, 2013;Kizito et al, 2015;Garner et al, 2015). In addition, a Inappropriate healthy work environment is one of the effective factors in maintaining nurses, and Inappropriate healthy work environment is one of the reasons related to the migration of nurses (Freeman et al, 2012;Dywili et al, 2013;Scruth et al, 2018;Hall et al, 2019;).…”
Section: Discussionsupporting
confidence: 91%
“…Reasons related to the work environment were the most frequent cause of migration in the context of migration of human resources in the health sector. Lack of equipment and facilities in hospitals, high numbers of patients, high-risk environment, safety at work ( 21 ); job satisfaction, better working environment abroad, better management abroad, pressure of colleagues in the country of origin, high working hours and heavy workload, job position ( 22 ); improvement of workplace status ( 23 ); the status of current job satisfaction ( 24 ); poor employment conditions in the country of origin ( 25 ) and to advance career and job status ( 26 ) were all reasons related to occupational factors mentioned in various studies as reasons for migration among workers in health resources. Therefore, to keep employees in the country, work environments must be taken into special consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these factors were completely beyond the control of the health system, and related to society at the macro level. In a study conducted in Uganda on migration of physicians, it was found that one reason for inclination to migrate among medical students was political considerations ( 21 ). A study in Pakistan on medical students, revealed that discrimination and religious reasons caused migration ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have quantified factors that propel physician migration from source countries: access to better training opportunities, higher salaries, need to escape political instability and corruption, poor quality of facilities and equipment, and plans for raising children [5][6][7][8]. Conversely, factors that influence physician retention in the destination countries include strong and robust health systems and political stability, which tend to facilitate improved lifestyles and opportunities for physicians and their families.…”
Section: An Ethical Dilemma Training Programs Create For Internationamentioning
confidence: 99%